Penerapan Sistem Informasi Akuntansi atas Profitabilitas di Bank Syariah Indonesia - Sinaga, Imelda; Suharsana, Yohannes; Tania, Elisabeth Lusi (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine the significant influence of SIA (Accounting Information System) in the form of total assets, working capital, earnings after tax, net operating assets, capitalization and cost efficiency on return on equity (RoE) of sharia banking. The sample in this study consisted of 45 Islamic bank financial reports registered with the Financial Services Authority (OJK) during the 2018-2022 period. The research method uses multiple linear regression. The research results reveal that there is an influence of the Accounting Information System, in this case the capitalization and cost efficiency variables, on return on equity (RoE) at Bank Syariah Indonesia.